Perencanaan Jaringan Akses Optik Ftth Menggunakan Teknologi Gpon (Gigabit Passive Optical Network) - Prasta Mahrifatika; Iqbal Maulana; Khaila Mardina Fauziah; Didik Aribowo (Universitas Katolik Widya Karya Malang, 2023)
The development of information and communication technology is increasing rapidly from year to year, especially in the field of telecommunications. Communication technology via fiber optic is one of the technologies that is widely used as a data sender, between senders and receivers in one network, users can communicate with each other at very high speeds. This is in line with the community's need for fast communication services. FTTH (Fiber To The Home) is a telecommunications service infrastructure that supports transmission on large bandwidths and can solve bandwidth access problems so that PT. Telkom designs fiber to the home network access using GPON technology by determining its usage.